Comparative Genomic Analysis of TCP Genes in Six Rosaceae Species and Expression Pattern Analysis in Pyrus bretschneideri - Zhao, Yu; Su, Xueqiang; Wang, Xinya; Wang, Mengna; Chi, Xujing; Aamir Manzoor, Muhammad; Li, Guohui; Cai, Yongping (Frontiers in Genetics, 2021)
TCP is a plant-specific transcription factor that plays an important role in flowering, leaf development and other physiological processes. In this study, we identified a total of 155 TCP genes: 34 in Pyrus bretschneideri, 19 in Fragaria vesca, 52 in Malus domestica, 19 in Prunus mume, 17 in Rubus occidentalis and 14 in Prunus avium. The evolutionary relationship of the TCP gene family was examined by constructing a phylogenetic tree, tracking gene duplication events, performing a sliding window analysis. The expression profile analysis and qRT-PCR results of different tissues showed that PbTCP10 were highly expressed in the flowers. These results indicated that PbTCP10 might participated in flowering induction in pear. Expression pattern analysis of different developmental stages showed that PbTCP14 and PbTCP15 were similar to the accumulation pattern of fruit lignin and the stone cell content. These two genes might participate in the thickening of the secondary wall during the formation of stone cells in pear. Subcellular localization showed that PbTCPs worked in the nucleus. This study explored the evolution of TCP genes in six Rosaceae species, and the expression pattern of TCP genes in different tissues of “Dangshan Su” pear. Candidate genes related to flower induction and stone cell formation were identified. In summary, our research provided an important theoretical basis for improving pear fruit quality and increasing fruit yield by molecular breeding.